Estasobasofobia: An interpretation of Gonzalo Portals’ poetry collection Voces y uwans (2015) from Walter Benjamin’s Dialectical Image - Durand Ato, David (2024)
This article makes an interpretation, from the perspective of Walter Benjamin’s concept of dialectical image, of Gonzalo Portals’ collection of poems Voces y uwans [collected in the shadow of a lily] (2015). To this end, we will seek to identify contradictory elements, such as illness, desire, dream (or nightmare), urban constellations, that is, the city, among other aspects that constitute a catastrophic scenario and that can only be observed with poems, in the style of film montage, that imitate the kaleidoscope. It is assumed that the collection of poems is not only difficult to read, but that it is an avant-garde experience related to surrealism. However, an attempt is made to show fragments that, intertwined with others, build a common thread that allows us to find that contradictory and dialectical view between the present and the repressed past, and above all its multiple tensions, where the central axis is the illness, not not only that of the body, but of society in general.